Phosphate (Pi) stress‐responsive transcription factors PdeWRKY6 and PdeWRKY65 regulate the expression of PdePHT1;9 to modulate tissue Pi concentration in poplar. (6th August 2022) - Yang, Xiaoqing; Zhang, Keai; Nvsvrot, Tashbek; Zhang, Yan; Cai, Guanghua; Huang, Liyu; Ren, Wenyu; Ding, Yiwei; Hammond, John P.; Shi, Lei; Wang, Nian
SUMMARY: Phosphorus (P) is an important nutrient for plants. Here, we identify a WRKY transcription factor (TF) in poplar ( Populus deltoides × Populus euramericana ) (PdeWRKY65) that modulates tissue phosphate (Pi) concentrations in poplar. PdeWRKY65 overexpression (OE) transgenic lines showed reduced shoot Pi concentrations under both low and normal Pi availabilities, while PdeWRKY65 reduced expression (RE) lines showed the opposite phenotype. A gene encoding a Pi transporter (PHT), PdePHT1;9, was identified as the direct downstream target of PdeWRKY65 by RNA sequencing (RNA‐Seq). The negative regulation of PdePHT1;9 expression by PdeWRKY65 was confirmed by DNA–protein interaction assays, including yeast one‐hybrid (Y1H), electrophoretic mobility shift assay (EMSA), co‐expression of the promoters of PdePHT1;9 and PdeWRKY65 in tobacco ( Nicotiana benthamiana ) leaves, and chromatin immunoprecipitation–quantitative PCR. A second WRKY TF, PdeWRKY6, was subsequently identified and confirmed to positively regulate the expression of PdePHT1;9 by DNA–protein interaction assays. PdePHT1;9 and PdeWRKY6 OE and RE poplar transgenic lines were used to confirm their positive regulation of shoot Pi concentrations, under both normal and low Pi availabilities. No interaction between PdeWRKY6 and PdeWRKY65 was observed at the DNA or protein levels. Collectively, these data suggest that the low Pi‐responsive TFs PdeWRKY6 and PdeWRKY65 independently regulate the expression of PHT1;9 to modulate tissue Pi concentrations in poplar. Significance Statement: The genes PdeWRKY65 and PdeWRKY6, encoding WRKY transcription factors, and PdePHT1;9, encoding a phosphate (Pi) transporter, form a regulatory network to modulate tissue Pi concentrations in response to low Pi availability in poplar ( Populus deltoides × Populus euramericana ). In the regulatory network, PdeWRKY65 and PdeWRKY6 negatively and positively regulate the expression of PdePHT1;9 by binding to W‐Boxes within the PdePHT1;9 promoter, respectively.